Occurence and relative dominance of pathogens in rhizome rot of ginger at Ranchi - and R.B. SHARMA, SAVITA EKKA, S.M PRASAD* (Indian Phytopathology, 2009)
Surveys were undertaken during Kharif, 2003-04 and 2004-05 crop seasons to cover ginger growing areas in Ranchi district in ginger plots to record rhizome rot disease. Maximum number of infected plants were recorded. Pure culture were obtained from infected fields. Out of a total of 135 isolations made from infected rhizomes 67 samples yielded Pythium spp. 33 yielded Fusarium spp. and the remaining 35 yielded Ralstonia solanacearum. In case of pseudo stem, 55 samples yielded Pythium spp. 22 Fusarium spp and remaining 24 yielded Ralstonia. While from sick soils, 47 samples yielded Pythium spp., 13 Fusarium spp. and 11 samples yielded Ralstonia solanacearum. The result indicated association of Pythium, Fusarium and Ralstonia with local variation in regard to dominance of Pythium aphanidermatum as compared to F. oxysporum f.sp. zingiberi and R. solanacearum in the region.